Lafal Layta dalam Al-Qur’an - Syukran Abu Bakar; Syarifah Maysarah (TAFSE: Journal of Qur'anic Studies, 2020)
This article is a research about the word of layta in the Qur’an. Generally, the use of the word of layta in the Qur'an referred to unbelievers when expressing their remorse in the afterlife. However, there are Qur'an verses that use the word of layta referred to the believers and in the context of the world. Due to the variations of this designation, the author feels the need for more in-depth research related to the use of the word of layta in the Qur'an. This research is library research, using content analysis techniques in processing data. The data sources that the authors refer to are Balâghah books such as al-Balâghat al-Wâdhihah, and the book of interpretation. The results of this study can be concluded that the word of layta is mentioned fourteen times in the Qur'an, with three speakers: believers, unbelievers, and hypocrites. The meanings indicated by this word are regret, delusion, and good wishes. Then, these meanings are connected with psychology. And the result is that if the pronunciation of this word relies on the believer, it shows a positive meaning, such as a sense of empathy. Conversely, if it relies on other than believers, it has a negative meaning. Tulisan ini merupakan penelitian terhadap lafal layta yang terdapat dalam al-Qur’an. Umumnya, penggunaan lafal layta dalam al-Qur’an disandarkan kepada orang-orang kafir ketika mereka mengungkapkan penyesalannya di akhirat. Namun, ada ayat al-Qur’an yang menggunakan lafal layta dengan disandarkan kepada orang mukmin dan dalam konteks dunia. Berangkat dari adanya variasi penyandaran lafal tersebut, penulis merasa perlu meneliti lebih dalam terkait penggunaan lafal layta di dalam al-Qur’an. Penelitian ini bersifat kepustakaan (library research), dengan menggunakan teknik analisa isi (content analysis) dalam mengolah data. Sumber data yang penulis rujuk adalah kitab-kitab Balâghah seperti  al-Balâghat al-Wâdhihah dan kitab-kitab tafsir. Hasil dari penelitian ini dapat disimpulkan bahwa lafal layta disebut sebanyak empat belas kali dalam al-Qur’an, yang disandarkan kepada tiga subjek, yaitu mukmin, kafir dan munafik. Makna yang ditunjukkan lafal layta adalah penyesalan, angan-angan dan harapan yang baik. Selanjutnya, makna-makna tersebut dihubungkan dengan ilmu psikologi. Maka, hasil yang didapatkan adalah jika pengucapan lafal ini disandarkan kepada orang mukmin, ia menunjukkan makna positif, seperti rasa empati. Sebaliknya, jika disandarkan kepada selain mukmin, maka ia bermakna negatif.